Implementing Social Media Marketing Strategy for Micro-Enterprise in Fashion Retail - Lady, Lady; Melsen, Fandion; Cuandra, Fendy (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This research aimed to enhance the online presence of Satia Collection, a micro-enterprise in Batam, Indonesia, through the strategic use of social media platforms. Accounts were established on Instagram, Facebook, Linktree, and Canva, accompanied by a new brand logo and Google Maps registration to improve customer accessibility. The implementation of Instagram ads led to a significant increase in reach and interaction on the platform, demonstrating tremendous customer engagement and the effectiveness of digital marketing strategies. Furthermore, there was a notable rise in WhatsApp messages through Instagram and Facebook links, highlighting the interconnectedness of these social media networks. The study emphasizes the importance of content quality over frequency in driving user engagement and underscores the need for retail entrepreneurs to leverage technological advancements. Among the social media networks, Facebook, WhatsApp, and Instagram emerged as the most-used platforms, with WhatsApp playing a crucial role in customer-centered marketing due to its affordability and ease of use.